Acidic Pit Lakes The Legacy of Coal and Metal Surface Mines - Geller, Walter; Schultze, Martin; Kleinmann, Robert; Wolkersdorfer, Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This monograph provides an international perspective on pit lakes in post-mining landscapes, including the problem of geogenic acidification. Much has been learned during the last decade through research and practical experience on how to mitigate or remediate the environmental problems of acidic pit lakes. In the first part of the book, general scientific issues are presented in 21 contributions from the fields of geo-environmental science, water chemistry, lake physics, lake modeling, and on the peculiar biological features that occur in the extreme habitats of acidic pit lakes. Another chapter provides an overview of methods currently used to remediate acidic pit lakes and treat outflowing acidic water. The second part of the book is a collection of regional surveys of pit lake problems from three European countries and Australia, and case studies of various individual representative lakes. A final case study provides an innovative approach to assessing the economic value of new pit lakes and balancing the costs and benefits, a valuable tool for decision makers.
Terrestrial Environment of Pit Lakes -- Limnology of mining lakes -- Remediation and Management of Acidified Pit Lakes -- Regional Surveys and Case Studies -- Lessons Learned, Open Questions and Concluding Remarks.
Keywords: Geography; Earth Sciences; Environmental Science and Engineering